THE EFFECT OF BRAND IMAGE, DISCOUNTS, CUSTOMER ADVOCATE, AND LOYALTY PROGRAMS ON CUSTOMER LOYALTY OF TELKOMSEL USERS IN LHOKSEUMAWE CITY - Ananda Rizky; Adnan; Maryudi; Muchsin (RADJA PUBLIKA, 2025)
This study aims to determine the Influence of Brand Image, Discount, Customer Advocate and Loyalty Program on Customer Loyalty of My Telkomsel Users in Lhokseumawe City. The data in this study are primary data obtained from distributing questionnaires to users of the My Telkomsel application. The population in this study is unknown, and using the hair formula, 100 respondents were obtained. The instrument measurement tool in the study is a Likert scale. This study uses non-probability sampling because the population is not known for certain. The sampling method used is purposive sampling. Data analysis techniques in the study used multiple linear regression analysis, Classical Assumption Test, and hypothesis testing and determination coefficients were carried out using the SPSS version 26 program. and the results of the study showed that Brand Image has a positive and significant effect on Customer Loyalty, this is evidenced by the t count value> t table (3.302> 1984) and a significant value of 0.001 <0.05, Discount has a positive and significant effect on Customer Loyalty, this is evidenced by the t count value> t table (3.533> 1984) and a significant value of 0.001 <0.05, Customer Advocate has a positive and significant effect on Customer Loyalty, this is evidenced by the t count value> t table (3.769> 1984) and a significant value of 0.001 <0.05 and Loyalty Program has a positive and significant effect on Customer Loyalty, this is evidenced by the t count value> t table (3.922 > 1984) and a significant value of 0.002 < 0.05. For further research, it is possible to add existing samples and expand the research location and variables to obtain more accurate research results.